Effect of Post-Harvest Preservation and Extraction Methods on Antioxidant Properties of Alternanthera Sessilis Red - Shaharuddin, Syafiqah; Othman, Azizah; Nor I’zzah Wan Mohd Zain, Wan (International Journal of Engineering and Technology, 2019)
Herbs with antioxidant properties are usually preserved and extracted before being converted into commercial products. The main focus of this study was to determine the effect of preservation of A. sessilis red as well as extraction method on its antioxidant properties. A. sessilis red was preserved using two different methods; freeze drying and superheated steam drying, followed by extraction with 70% ethanol using conventional extraction and ultrasonic-assisted extraction. Drying in the superheated steam oven displayed shorter drying period of 1 hour compared to freeze drying (several days). Combination of superheated steam drying and ultrasonic-assisted extraction showed the highest extraction yields (12.99%). Results showed that superheated steam drying and ultrasonic-assisted extraction displayed an increase in the total phenolic content. In terms of antioxidant capacity, A. sessilis extracts obtained from superheated steam drying has higher radical scavenging activity (72.39% - 76.70%) than those freeze-dried (60.68% - 65.33%). Meanwhile, ultrasonic-assisted extraction had negatively impacted the radical scavenging activity of the extracts due to the formation of free radicals that are related to acoustic cavitation. As for ferric reducing antioxidant power, both superheated steam drying and ultrasonic assisted extraction yielded extracts with greater capacity. Present result shows that the combination of superheated steam drying and ultrasonic-assisted extraction enhanced total phenolic content by 60% and improved antioxidant activity based on ferric reducing antioxidant power assayÂ